Understanding the role of gibberellin signalling in wheat anther development during heat stress - Audley, Matthew David (2017)
High temperature (HT) stress during wheat male reproductive development causes irreversible damage to the anther tapetum layer and the developing microspores it supports, resulting in reduced yield. With the frequency of pre-flowing temperature stress events likely to increase, a better understanding of the effects of high temperature stress on anther developmental regulation is required. Gibberellin (GA) signalling has been shown to regulate tapetum programmed cell death (PCD) and pollen coat formation via the transcription factor (TF) GAMYB. This project aimed to investigate the function of two putative GA-signalling components in wheat anther development and characterise the global hormonal and transcriptional anther responses to HT. RNAi and TILLInG mutants for TaGAMYB and a putative orthologue of a rice tapetum PCD component, TabHLH141, revealed that both are required for male fertility. Tagamyb mutants displayed stunted anther development with irregular tapetum vacuolisation and reduced pollen viability. An interaction between RHT-D1 and TabHLH141 suggests that GA may mediate anther development through regulation of DELLA-TF interactions. Having characterised and developed a non-destructive staging method for wheat anther development, RNA-Seq and global hormone analysis was used to investigate the response to HT stress around pollen mother cell meiosis. Significant changes in expression of tapetum metabolism and PCD annotated transcripts and anther GA, auxin and jasmonate concentrations indicates that hormonal regulation of HT-responsive transcription may contribute to defective anther development. The work in this project demonstrates that advanced functional genomics techniques can be now be applied to the dissection of complex signalling pathways in hexaploid wheat.